PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI PEMBENTUKAN KOPERASI PADA ANGGOTA ORKI TANGERANG SELATAN - Agus Sudarsono; Abdul Khoir; Suhandi (Abdi Jurnal Publikasi, 2025)
The purpose of this community service is to increase public knowledge about cooperatives in order to improve the family economy. The method of implementing this community service is counseling related to the formation of cooperatives. The partners of this community service are groups of community institutions engaged in sports and fitness in South Tangerang. The evaluation instrument for the activity uses a pre-test and post-test which are then analyzed descriptively. The results of this community service show that there is an increase in the knowledge of members of the activity related to cooperatives by 65%, an increase in knowledge of the stages of forming a cooperative by 35%. In addition, the participants have the motivation to improve the family economy through the formation of cooperatives in their organizations.